Potential use of plasma focus radiation sources in superficial cancer therapy - Poh, H. S.; Lee, M. C.; Yap, S. S.; Teow, Sin Yeang *; Bradley, D.A. *; Yap, S. L. (IOP, 2020)
The new multidisciplinary field of plasma medicine combines plasma physics, electrical engineering, life sciences and clinical medicine. Here we explore potential uses in medicine, most particularly cancer therapy, the plasma source being brought out of the field of industrial applications into the life sciences, the focus being on superficial cancer radiotherapy strategies. Existing radiotherapy practices for such cancers rely on the use of rather large facilities, most popularly the electron linear accelerator and X-ray tube-based devices. Conversely, a compact plasma radiation source can be housed in a relatively small space, there being considerable promise for such devices to produce the fluence requirements of radiotherapy for treatment of skin cancers. The present study of feasibility investigates the plasma focus device, with the emission produced by a single discharge shown to generate an X-ray dose of few tens of mGy. The X-ray dose is the integration of emission in the discharge durations of less than a μs, it is therefore possible using these devices to build up fractional irradiation dose through repetitive operation of the discharge system.